Integration of Applications and Social Media in Arabic Language Learning - Syahabuddin Nur; Saipul Rahman (PT. Global Pustaka Ilmiah, 2026)
This study aims to analyze the integration of digital learning applications and social media in Arabic language learning in the digital era. This research employs a qualitative approach using library research methods with descriptive-analytical analysis. The formal object of this study is the concept of technology integration in education, while the material object focuses on the use of digital applications and social media in Arabic language learning. The scope of the study includes various platforms such as learning applications (Wattpad, Canva, Google Classroom, Kahoot, and others) and social media (WhatsApp, Instagram, TikTok, YouTube, and Facebook). The research context lies in utilizing technology to enhance more interactive and contextual Arabic learning. The results show that the integration of digital applications and social media can increase learning motivation, create more flexible and interactive learning environments, and provide broader access to authentic materials. However, challenges such as limited technological access, social media distractions, and low digital literacy are still encountered. This study concludes that well-planned and controlled integration of learning applications and social media can create more effective, innovative, and relevant Arabic language learning in the digital era.